Pengaruh Layanan Bimbingan Klasikal Menggunakan Cooperative Games (Team Building) Terhadap Peningkatan Kohesivitas Kelompok Siswa Di Kelas X SMA Negeri 1 Selong - Alpian Wahyudi; Baiq Mahyatun; Maulidiana Zain (EDUCARE: Jurnal Pendidikan dan Kesehatan, 2026)
Group cohesiveness is an important aspect in supporting cooperation, communication, a sense of togetherness, and interpersonal bonds among students during classroom interactions. This study was motivated by the relatively low level of group cohesiveness among some students in class X.10 of SMA Negeri 1 Selong, as indicated by limited cooperation, communication, sense of togetherness, and attachment among group members. This study aimed to determine the effect of classical guidance services using cooperative games (team building) on improving students’ group cohesiveness. The study employed a quantitative approach with an experimental method and a pre-experimental one-group pretest-posttest design. The participants were 32 students of class X.10 at SMA Negeri 1 Selong selected through nonprobability sampling using incidental sampling. Data were collected using a Group Cohesiveness Questionnaire developed based on the dimensions of cohesiveness proposed by Forsyth and analyzed using SPSS version 27 through the Shapiro-Wilk normality test and Paired Sample t-Test. The normality test results indicated that the pretest and posttest data were normally distributed, with significance values of 0.320 and 0.504, respectively. The Paired Sample t-Test showed a t-value of -24.166 with a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference between the scores before and after the intervention. Therefore, classical guidance services using cooperative games (team building) had a significant effect on improving the group cohesiveness of students in class X.10 at SMA Negeri 1 Selong.